Secondary Osteoporosis in Patients with Juvenile Idiopathic Arthritis - Kristyna Brabnikova Maresova (Journal of Osteoporosis)
Bone disease in patients with juvenile idiopathic arthritis (JIA) is associated with focal (joint erosion and juxtaarticular osteopenia) and systemic bone loss (generalized osteopenia or reduction of bone mass density). Pathophysiology of bone loss is multifactorial and involves particularly proinflammatory cytokines and deleterious effects of glucocorticoid therapy. Clinical studies in patients with JIA indicate excessive activation of osteoclastogenesis and reduction of bone formation. Reduction of physical activity, muscle atrophy caused by high disease activity, and compulsory restriction in movements are also associated with bone loss. In patients with JIA, the disease can be complicated by growth cartilage involvement and systemic or local growth retardation. In the absence of preventive measures, fragility fractures can occur even at an early age.